Role of Strength and Aerobic Sports Activity in Preventing Cachexia in Breast Cancer Survivors: A Review Study - Samira Emadi; Zahra Hemati Farsani; Farzaneh Movaseghi (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: Cachexia syndrome is a multifactorial syndrome characterized by a significant reduction in skeletal muscle mass and no reduction in body fat mass. Therefore, the present s tudy aimed to inves tigate the therapeutic effect of sports exercises on the mechanisms that cause cachexia. Methods: In the review and narrative s tudy, PubMed, Springer, Elsevier, Science Direct, and SID databases from 1991 to 2022 were searched using the keywords "Physical fitness, physical activity, muscle, body composition, breas t cancer, and exercise." After the initial screening, the full text of the articles was evaluated, and the articles that met the inclusion criteria were analyzed. A total of 67 articles met the inclusion criteria for the review. Results: Based on recent studies, the mos t important possible mechanisms affecting cancer cachexia are sys temic cytokines, which are continuously activated by cancer and its treatment. Research shows that exercise may prevent cachexia in cancer patients.                                                 Conclusion: Skeletal muscle loss due to cancer cachexia is clinically important since it helps reduce or discontinue cancer treatment and is associated with increased mortality. It seems that performing sports interventions can be effective in improving these complications.